The difference of VO2Max and immune profile (Hmbgl, cortisol, ll-6, Tnf alpha, number of leukocytes, neutrophils and monocytes) in adolescents who were trained and untrained in basketball - Huldani, H.; Pattelongi, I.; Massi, M. N.; Idris, I.; Bukhari, A.; Sinrang, A. W.; Arsyad, A.; Widodo, A. D. W.; Achmad, H.; Bahar, B. (Journal of Human Sport & Exercise, 2021)
This study was conducted to see differences in VO2max values and differences in levels of HMGB1, cortisol, IL6, TNF alpha, and the number of leukocytes, neutrophils and monocytes after moderate intensity aerobic exercise (70-79% MHR) for 12 minutes. The study used a cross-sectional study method and purposive sampling method on 15 basketball-trained students and 15 basketball untrained students at SMAN 1 Banjarbaru with an average age of seventeen years. Measurement of VO2max value was done on the first day with MFT (Multistage Fitness Test / Bleep Test). The levels of HMGB1, cortisol, IL6, TNF alpha, the number of leukocytes, neutrophils, and monocytes were measured on the third day by taking blood after students did aerobic exercise with moderate intensity running for twelve minutes. Data were analysed using the Mann Whitney test for VO2max, cortisol, IL6, TNF Alfa, and leukocyte and monocyte counts and unpaired t test for HMGB1 and neutrophils. The results indicate that the average VO2max, HMGB1, IL6, and cortisol scores of basketballs trained students are higher than those who were not trained. ln contrast, the TNF alpha, leukocytes, neutrophils and untrained monocytes are higher in levels and numbers. There are significant differences in trained students basketball and untrained (p < .05) on VO2max, cortisol, and TNF alpha. Not There was a significant difference (p > .05) after intensity aerobic exercise being twelve minutes on students trained in basketball and not trained for HMGB1, IL6, leukocyte count, neutrophils, and monocytes. This study indicates that basketball-trained students have better VO2max scores than untrained basketball students. Cortisol levels were higher in basketball-trained students compared to basketball-untrained students in 12 minutes of moderate-intensity aerobic exercise, while TNFalpha levels were the opposite. 12 minutes of aerobic exercise as a method of choice to increase the body's immune system and show students the homeostatic process is going well.